The Effect of Tectonic Stress and Thermal Evolution on Shale Pores of Devonian and Carboniferous Shales in Southern China. (8th June 2022) - Zhang, Zhiyao; Xu, Shang; Shi, Wanzhong; Meng, Fanyang; Gou, Qiyang; Zhao, Mingfang
Abstract : Many sets of Paleozoic marine organic-rich shale strata are developed in southern China. However, the exploration and development degree of these strata are different. Cambrian shale and Ordovician-Silurian shale are two horizons with high degree of exploration, while Devonian shale and Carboniferous shale exploration is deficient. Based on XRD, FE-SEM, and gas adsorption experiment, pore development characteristics and controlling factors of Devonian and Carboniferous shale are investigated. There are mainly four lithofacies in Devonian and Carboniferous shale: mixed shale (M), carbonate/siliceous mixed shale (M-1), argillaceous/siliceous mixed shale (M-2), and argillaceous-rich siliceous shale (S-3). Reservoir characteristics of both two sets of shale strata are quite different. The averages of porosity, pore volume, and specific surface area of Devonian shale are 3.81 %, 9.7 × 10 − 3  cm 3 /g and 11.8 m 2 /g, while those of Carboniferous shale are 3.57%, 17.3 × 10 − 3  cm 3 /g and 19.8 m 2 /g. Thermal evolution (Ro) and tectonic preservation conditions are the main factors affecting the pore development. Carboniferous shale (Ro ≈ 2 % ) is in the stage of producing a large number of organic pores. Devonian shale (Ro ≈ 3.5 % ) is having difficulty preserving organic pores due to high thermal evolution. Meanwhile, Devonian shale (well GTD1) is strongly affected by tectonic movement; tectonic fractures and calcite veins are developed. Carboniferous shale (well GRY1) is in relatively stable area; tectonic fractures are not developed. Under the influence of compaction, the pore volume and specific surface area of Carboniferous shale are 78.3% and 67.8% higher than those of Devonian shale, respectively. This research can provide reference for clarifying shale pore development and evolution mechanism and similar shale gas exploration both in study area and around the world.